The Impact of Public Research Units on Regional Innovation Processes and Regional Economic Development - Martin T.W. Rosenfeld; Diana Roth (European Regional Science Association (ERSA), 2004)
It is well-known today that innovation activities of private firms play a significant role for economic growth in less-developed regions. There are many studies on these interrelations and on explaining how regional innovation processes are working and which factors are important for them. However, some important questions have still not been completely answered by these studies. One of these questions is that of the role of public research units (PRU, which include publicly financed universities and research institutes) in the process of regional innovation. There have already been several studies on the economic impacts of selected PRU on economic growth. But it is not comprehensively answered so far to what extent the impact on economic growth of a PRU is concentrated on the region where the PRU itself is located. In other words: Whether the ”knowledge transfers offered by a PRU will have more effects on firms located nearby (at a small distance from the PRU) than on firms at other locations - or if other factors than spatial distance are more important for the decision of private firms to use knowledge transfers from certain PRU. The paper presents the results of a research project for answering this question for the case of the Halle region (= the southern part of the German Land Saxony-Anhalt). It is based on an empirical analysis (two postal surveys on PRU and on knowledge-based private firms) with a focus on the most important types of knowledge transfers. For those firms which are cooperating with PRU, if it is shown that spatial distance is an important factor, in the sense that firms which are located nearer to the PRU are cooperating more intensively with the PRU than firms which are located in other regions. But also important for the firms is the import of knowledge transfers from PRU which are located outside Saxony-Anhalt. With regard to the determining factors which are important for the spatial direction of knowledge transfers, it is shown that apart from spatial proximity, also various factors on the demand side may inhibit knowledge transfers. Therefore, for being effective, regional policy should also deal with the demand side (and not just with public research units) to create better conditions for knowledge transfers in structural weak regions.
Keywords: 330